Multiply this polynomial step-by-step, (6x + 7)(3x +2)

(6x + 7)(3x +2)
= 18x^2 + 21x + 12x + 14
= 18x^2 + 33x + 14

andrewpallarca|Points 20171|

Question

Asked 3/10/2013 11:49:14 PM

Updated 7/7/2014 7:14:03 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [7/7/2014 7:14:02 PM], Confirmed by andrewpallarca [7/7/2014 7:14:03 PM]

Rating

There are no new answers.

Add or subtract the following polynomials. (5.9x to 3rd power + 3.4x to 2nd power - 7) - (2.9x to 3rd power - 9.6x to 2nd power + 3) **Weegy:** (5.9x^3+3.4x^2-7)-(2.9x^3-9.6x^2+3)
=(45x^3 +12x^2 -7) -(18x^3-54x^2+3)
remove the paranthesis
=45x^3+12x^2 -7 -18x^3 +54x^2 -3
take the like terms together and simplify
45x^3-18x^3 +12x^2+54x^2 -7-3
=> (45-18)x^3 + (12+54)x^2 -(7+3)
=> 27x^3 + [ 66x^2 -10 ] **User:** multiply this polynomials - (6x + 7)(3x + 2), step-by-step **Weegy:** x = 12/6 = 2 (More)

Question

Expert Answered

Updated 6/22/2014 4:04:39 AM

1 Answer/Comment

- (6x + 7)(3x + 2)

= -(18x^2 + 12x + 21x + 14)

= -(18x^2 + 33x + 14)

= -18x^2 - 33x - 14

= -(18x^2 + 12x + 21x + 14)

= -(18x^2 + 33x + 14)

= -18x^2 - 33x - 14

Added 6/22/2014 4:04:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/22/2014 10:31:04 AM]

27,087,852

questions answered

There are no comments.